(untitled) (Journal of Partial Differential Equations, 2005)
We study the structure and behavior of non-negative radial solution for the following elliptic equation Δu = u^ν, x ∈ R^n with 0 < ν < 1. We also obtain the detailed asymptotic expansion of u near infinity.